The Impact of Motivational Interviewing and MOTIVE Tool Use by Pharmacists on Vaccine Acceptance - Aleda M. H. Chen; Alea Anthony; Adeola Balogun; Ruth Pereira; Justin W. Cole (MDPI AG, 2024)
Vaccines have played a significant role in reducing infectious disease burden. However, vaccine hesitancy remains a persistent challenge in public health, including for pharmacists who often interact with patients regarding vaccines. Thus, this study assesses the impact of motivational interviewing (MI) training and the MI-based vaccine hesitancy discussion tools (MOTIVE) on pharmacists' management of vaccine hesitancy. Pharmacists in eight Midwestern pharmacy practices who completed MI and MOTIVE training and engaged with vaccine-hesitant patients participated in this study. The pharmacist participants completed post-encounter surveys identifying the vaccine discussed, the tool utilized, and the outcome of the conversation. Descriptive results from 362 encounters indicated that the primary reasons for hesitancy were safety (39%), care coordination (31.5%), and efficacy (30.4%). Post encounter, 35.4% of patients received vaccines, 26% planned to, 25.1% considered it, and 13.5% were uninterested. The findings highlight the importance of patient-centered communication, such as MI, between patients and pharmacists to identify and address reasons for vaccine hesitancy. Pharmacists, equipped with conversation tools such as the MOTIVE tools, may effectively influence vaccine acceptance. Future research should evaluate the utility of MI and the MOTIVE tools in other settings and regions.